2021
DOI: 10.1097/sla.0000000000005157
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Low Molecular Weight Heparin Versus Unfractionated Heparin for Prevention of Venous Thromboembolism in Trauma Patients

Abstract: Trauma patients are at high risk of VTE. We summarize the efficacy and safety of LMWH versus UFH for the prevention of VTE in trauma patients. Methods: We searched 6 databases from inception through March 12, 2021. We included randomized controlled trials (RCTs) or observational studies comparing LMWH versus UFH for thromboprophylaxis in adult trauma patients. We pooled effect estimates across RCTs and observational studies separately, using random-effects model and inverse variance weighting. We assessed risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 76 publications
0
31
0
Order By: Relevance
“…[4][5][6][7] Historically, enoxaparin 30 mg subcutaneously (SUBQ) every 12 h has been the most common dosing regimen used in clinical practice for trauma patients. [2][3][4][5]8,9 Yet, current literature suggests that higher doses may be required to achieve anti-Factor Xa (anti-Xa) targets and further reduce VTE complications. [10][11][12][13][14][15][16] The clinical practice algorithm from the Western Trauma Association (WTA) was released in November of 2020 and was the first guideline update to recommend a higher standard initial enoxaparin dose; however, we hypothesize that implementation of these dosing recommendations has not occurred consistently in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Historically, enoxaparin 30 mg subcutaneously (SUBQ) every 12 h has been the most common dosing regimen used in clinical practice for trauma patients. [2][3][4][5]8,9 Yet, current literature suggests that higher doses may be required to achieve anti-Factor Xa (anti-Xa) targets and further reduce VTE complications. [10][11][12][13][14][15][16] The clinical practice algorithm from the Western Trauma Association (WTA) was released in November of 2020 and was the first guideline update to recommend a higher standard initial enoxaparin dose; however, we hypothesize that implementation of these dosing recommendations has not occurred consistently in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, compared to UH, LMWH may reduce PE (adjusted OR 0.56, 95% CI 0.50–0.62) and mortality (adjusted OR 0.54, 95% CI 0.45–0.65). In keeping with the results reported by Tran et al [ 50 ], Jakob et al [ 51 ] analyzed data of 4074 patients with blunt isolated severe liver injuries selected for NOM who received VTE prophylaxis with either UH or LMWH. Notably, LMWH was independently associated with lower mortality (OR 0.36) compared to UH.…”
Section: Methodsmentioning
confidence: 92%
“…Regarding the choice between LMWH versus UH, indirect evidence from general trauma cases and liver trauma suggests that LMWH is superior to UH for DVT and VTE prevention and may additionally reduce PE and mortality. A recent systematic review and meta-analysis [ 50 ] that included four randomized trials for a total of 879 patients and eight observational studies (306,747 patients) found that, based on pooled randomized data, LMWH reduces DVT (RR 0.67, 95% CI 0.50–0.88, moderate certainty) and VTE (RR 0.68, 95% CI 0.51–0.90, moderate certainty) compared to UH. Moreover, compared to UH, LMWH may reduce PE (adjusted OR 0.56, 95% CI 0.50–0.62) and mortality (adjusted OR 0.54, 95% CI 0.45–0.65).…”
Section: Methodsmentioning
confidence: 99%
“…Both registry data and a meta-analysis of prospective and retrospective data supports the administration of LMWH over unfractionated heparin for VTE prophylaxis in all trauma patients. 10,12 Jacobs et al found decreased odds of not only mortality but also PE and DVT for LMWH compared to unfractionated heparin in an analysis of the Michigan Trauma Quality Improvement Program. 12 Additional data supporting the use of LMWH over unfractionated heparin comes from studies of spine trauma patients and patients who sustain traumatic brain injuries.…”
Section: Discussionmentioning
confidence: 99%